Loss measurements on semiconductor lasers by Fourier analysis of the emission spectra - Hofstetter, Daniel; Thornton, Robert L. (My University, 1998)
We present a study on a novel method for the determination of the cavity losses in semiconductor lasers. The method we use involves Fourier analysis of the Fabry–Pérot mode spectrum when operating the device below lasing threshold. The observation of the decay rate of higher order harmonics in the Fourier analysis of the spectra allows us to determine the amount of cavity propagation loss/gain. A comparison between experimental and calculated data for an AlGaInP laser at 670 nm showed good agreement up to an injection current of 0.93 × Ith. This method therefore provides a generalization of the Fabry–Pérot contrast measurement method for extracting cavity losses from spectral information.